Nationalsozialistische Schulverwaltung in Hamburg. Vier Führungspersonen - Schmidt, Uwe 1931-2008 (Hamburger Historische Forschungen, 2008)
After the change of power in Hamburg on March 8, 1933, the school administration was put under command of Karl Witt, a German nationalist and later Nazi. Converted to the National Socialist leadership principle, it was increasingly instrumentalized for the implementation of National Socialist educational concepts. These were mainly enforced by the persons who led the authority or dominated by informal power. The position of the four school-related officials in the power and governance system of National Socialism in Hamburg is therefore explained in this publication. Besides Karl Witt, three men were the protegés of the so-calld "Gauleiter" and "Reichsstatthalter" Karl Kaufmann: namely Wilhelm Schulz, Albert Henze, and Ernst Schrewe. Their proximity to the centre of power around Kaufmann led to very different formal and informal anchors in the mechanisms of the polycratic National Socialist system. The political pressure exerted by the head of the school administration on the schools intensified since the beginning of the war, culminating in the power and ruthless exercise of power by the National Socialist "Senatsdirektor" and "Gauschulungsleiter" Albert Henze